A new lateral load pattern for optimum design of concrete structures using the wave propagation theory. (June 2022) - Khaaloo, Alireza; Omidi, Hossein
Abstract: The current design procedure known as Force-Based Design (FBD) method, generally, does not lead to uniform distribution of drift, hysteretic energy, and ductility demands (or structural damage) along the height of the moment frames under strong earthquakes and these performance parameters can be much higher and concentrate damage on one or more of the lower structural stories. This paper presents an iterative wave propagation (WP) based technique to calculate the seismic nonlinear response of multistory buildings as an extension of the layered soil media, founded on bedrock and subjected to vertically propagating shear waves, which leads to the introduction of a new Lateral Load Pattern (LLP) for analysis and design of moment frames. In the proposed method, the stiffness and damping are assumed as displacement dependent variables, not as constant parameters, also, the method could extend to consider the soil-structure interaction (SSI). Targeting to achieve the almost equal ductility demand for different stories, the proposed LLP, focuses on changing stiffness and strength distributions simultaneously. Evaluating the amount of strain energy absorbed by different layers and also the displacement demand, the location and amount of cumulative damage caused in the structure could be calculated with appropriate accuracy and verified by Park-Ang Damage Index (PADI), as a cumulative concept that produces a more rational indication of the damage level, this paper also provided a more realistic modified PADI. Proposed LLP leads to better distribution of stiffness and strength along with the height of the structures and while the economical design; the more structural members contribute in energy dissipation. The low computational costs and high accuracy of the proposed method, besides the economic and optimal seismic design of structures, are the advantages of the proposed method.